E-Voting Inclusivity: The Accessibility of Elderly Voters in the 2021 Village Head Election in Sleman Regency - Tiara Fadilla; Tunjung Sulaksono (ARISTO, 2024)
The Village Head Election (Pilkades) is a forum for the community to use their voting rights to elect leaders at the village level. It utilizes technology as a tool to accelerate and influence the technicalities of village head elections from conventional to digital through electronic voting (e-voting). This research aims to analyze the accessibility of elderly voters in the Village Head Election in Sleman Regency, Special Region Province of Yogyakarta (DIY). This research was examined using Thomas and Penchansky's theory which consists of indicators of availability, accessibility and accommodation. This research was a qualitative type of research with data collection techniques using primary data, obtained from interviews, and secondary data, obtained from journal articles and other literature studies in the form of research-related documents. The results of this research show that the Sleman Regency’s Community Empowerment Service and the Village Government were the parties that provide facilities and infrastructure to the community in the village head election in Sleman Regency. In accommodating this, initially, the political dynamics in Sleman Regency were more apathetic and traditional for the elderly people due to the change of the era. However, after researching, the problems that arose during the election were more related to the technical aspects of e-voting rather than the community or elderly people. Several obstacles occurred during e-voting, making the voters annoyed. Then, the elderly voters were given the same services as the other voters, except for the elderly with limitations. In this case, indicators such as availability, accessibility, and accommodation are considered appropriate and sufficient for the needs of elderly people. Regarding these needs, the TTU (the main technical team) and TTL (the field technical team) try their best to fulfill whatever it is without discrimination.